(untitled) (Journal of Student Affairs in Africa, 2022)
Sub-Saharan Africa has the lowest higher education (HE) participation rate of any region in the world at under 10%. Large numbers of students are entering the various systems, often from non-traditional backgrounds, which contributes to making an already difficult transition even more difficult. In many instances, well-intended interventions and initiatives are imported from elsewhere or based on “common sense”, but they are often not very effective. This raises a crucial question: How can institutions best devise context-sensitive and effective student assistance programmes? Design-based research (DBR) uses an iterative and longitudinal process that involves theory, participant inputs, peer inputs and stakeholder inputs to cyclically develop theoretically informed, contextually sensitive and appropriate interventions. Most practitioners could benefit from a better understanding of this process when designing interventions. This article elucidates DBR as a phased intervention-development process aimed at assisting students to integrate into HE and focuses primarily on the methodological approach on which it elaborates using examples from a PhD study.